Metastatic Colorectal Cancer: Role of Target Therapies and Future Perspectives - Nappi, Anna; Berretta, Massimiliano; Romano, Carmela; Tafuto, Salvatore; Cassata, Antonino; Casaretti, Rossana; Silvestro, Lucrezia; Divitiis, Chiara D.; Alessandrini, Lara; Fiorica, Francesco; Ottaiano, Alessandro; Nasti, Guglielmo (Current Cancer Drug Targets, 2018)
Today, we are experiencing a real cultural revolution in the therapeutic approach to cancer of the colon - rectum, that by orphan disease, it is now becoming an important paradigm of scientific innovations and concepts. Survival of patients with metastatic colorectal cancer (m-CRC) has been significantly improved with the introduction of the monoclonal antibodies that have as target the vascular endothelial growth factor (VEGF) and the epidermal growth factor receptor (EGFR). The PD-1/PD-L1 pathway in cancer is implicated in tumors escaping immune destruction. This pathway is up -regulated in many tumours. Blockade of this pathway with anti-PD-1 and anti-PD-L1 agents has led to remarkable clinical responses in patients affected by many different types of cancer. The aim of this review is to evaluate the effects of addiction of biological agents to standard chemotherapy in the treatment of m-CRC. We can say that, among the various treatment options, the challenge of the future will be a better selection of the population, to ensure the best possible benefit from treatment with anti-VEGF drugs or anti-EGFR and a careful and customized planning of the therapeutic strategy for each patient.
Keywords: Colorectal cancer